2021
DOI: 10.4102/sajems.v24i1.3577
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and economic growth in South Africa: A cross-municipality panel data analysis

Abstract: Background:In the literature, human capital has been identified as a key economic variable that is needed to promote growth; hence this study explores the components of human capital, that is, different skill levels in order to capture the real effect of the employed labour on economic output across the municipalities of South Africa.Aim: This study investigates the effect of human capital of employed labour on economic output and growth in South Africa.Setting: The study focuses on the balanced panel of 269 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Abel et al (2019) adopt the error correction model for Zimbabwe from 1980 to 2015 and show that, human capital measured by government expenditure on health has a statistically significant and positive short run and long run effects on economic growth while government expenditure on education is negative. Ngepah et al (2021) explore the effects of human capital of employed labour on South African economic growth using data on 269 municipalities from 1993 to 2016. Applying the GMM estimation technique, the findings indicate that human capital measured by skilled employment leads to higher growth.…”
Section: Literature Review: Human Capital and Economic Growthmentioning
confidence: 99%
“…Abel et al (2019) adopt the error correction model for Zimbabwe from 1980 to 2015 and show that, human capital measured by government expenditure on health has a statistically significant and positive short run and long run effects on economic growth while government expenditure on education is negative. Ngepah et al (2021) explore the effects of human capital of employed labour on South African economic growth using data on 269 municipalities from 1993 to 2016. Applying the GMM estimation technique, the findings indicate that human capital measured by skilled employment leads to higher growth.…”
Section: Literature Review: Human Capital and Economic Growthmentioning
confidence: 99%
“…Mudassaar (2019) showed that human capital positively affects growth using a disaggregated sample of developing and developed countries in East, West, and South Asia. Ngepah et al, (2021) employing the GMM technique concluded that human capital facilitates growth in South Africca. Bawono (2021) also showed that human capital drives growth in Indonesia for the period 1984-2019 using autoregressive distributed lag (ARDL) method approach.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Aside migrant remittances being a driver of growth, human capital has also been identified as a key factor in attaining growth (Pelinescu, 2015;Kartal et al, 2017;Ngepah et al, 2021). Empirical studies have affirmed that human capital helps to develop an economy via expansion of skills and knowledge of its citizen.…”
Section: Introductionmentioning
confidence: 99%
“…The vitality of HC plays a central role in the competitiveness and success of organizations and countries (Flair 2022). Consequently, the economic growth and organizational outcomes of South African companies have also been significantly linked to HC (Ngepah et al 2021). Management and analysis of risks to this vital resource is thus imperative and seen as one of the most important conditions for maintaining company performance (Necula and Micu 2021).…”
Section: Introductionmentioning
confidence: 99%